Polityka w zakresie podatków samorządowych w latach 1991 - 2016 - Miszczuk, Magdalena (Polityka i Społeczeństwo, 2020)
The establishment of local governments in 1990 was accompanied by a separation of taxes for municipalities from public revenues. Local taxes are fiscally inefficient due to their specific construction, which triggers a question whether state tax policy does not marginalise them. The article refers to the introduced changes, as well as to the consequences of a chosen tax structure. In order to answer the aforementioned question, an analysis of regulations devoted to reforms in the system of local taxation, and of the extensive data of figures for years 1991–2016 has been conducted. The research does not unambiguously confirm the thesis that the state policy marginalises local taxes.